The Level of Environmental Trends among Students of The Faculty of Education Qasr Bin Ghashir in The Light of Some Variables - Dr. Karima Ramadan Faraj Abubaker (Journal of Scientific and Human Dimensions, 2026)
The aim of the research was to reveal the level of environmental trends among students of the Faculty of Education Qasr bin ghashir, and to identify the significance of differences in the level of environmental trends among students due to some variables such as(scientific specialization, number of semesters, studying the course of Environmental Psychology, and other courses related to the environment) and to achieve the objectives of the research, the researcher used the descriptive method, and the researcher prepared a questionnaire consisting of (3) areas (the field of environmental knowledge, the field of environmental problems, and the field of Environmental Protection), the (21) paragraphs, and were applied to a sample of (243) students distributed to (12) departments in After conducting statistical processing of the data, the results indicated : 1- The high level of environmental trends among the students of the Faculty of Education Qasr bin ghashir, which indicates that the students ’ attitudes towards the environment are positive. Their trends were high in the first area(environmental knowledge), while they were very high in the second and Third areas( environmental problems and Environmental Protection) . 2- There are no statistically significant differences between the averages of the responses of the research sample attributed to the scientific specialization variable of the female students, so the scientific specialization variable has nothing to do with the high level of environmental trends among the female students . 3- There are no statistically significant differences between the averages of the research sample responses attributable to the variable number of female students ’ classes. 4- there are statistically significant differences between the averages of the responses of the research sample attributed to the study of the Environmental Psychology course . 5- There are statistically significant differences between the averages of the responses of the research sample due to the study of courses related to the environment